Production of compost tea using washing machine disposal water - Ainul Asyira Saidin (Bintulu, Sarawak : Universiti Putra Malaysia, 2014)
The used of liquid fertilizer from wastewater especially washing machine disposal water might reduce water pollution. With emerging crisis of the water, washing machine disposal water could be one of the significant resources to be explored and studied. Abundance of agriculture waste has been generated from agricultural activities. This has increased managing cost, health issues and pollution. Thus, a study was conducted in the laboratory to produce different types of compost tea from washing machine disposal water. Ten different combinations of chicken dung and sawdust were prepared for composting. They were then placed in polystrene box before mixed with washing machine disposal water to produce compost tea. Data were analysed using statistical analysis software (SAS). Significant different of data were compared using Tukey Test at p<0.05. Results showed the ratios of the compost and washing machine disposal water have significantly affected the pH and nutrient contents of the compost tea. different types of compost tea can be produced by using washing machine disposal water however details study on the nutrients dissulation is required to confirm the findings.
Project Paper (B.S.Bi.) - Universiti Putra Malaysia Kampus Bintulu Sarawak, 2014.